(untitled) (International Journal of Environmental Sciences, 2025)
The present research study examined the reproductive health status of Scheduled Caste adolescent girls in Tamil Nadu and they determine on the socio-economic and cultural barriers and leading to limit their access to healthcare of the people in the nation. Findings reveal that approximately 65% of these girls lack knowledge about contraception, while 70% face challenges in menstrual hygiene management, leading to a reported 30% incidence of early pregnancies and a 25% prevalence of sexually transmitted infections. Despite initiatives like the Rastriya Kishor Swasthya Karyakram (RKSK) and the Menstrual Hygiene Scheme (MHS), their outreach and effectiveness remain insufficient among the adolescent girls. The study noticed that there is an urgent need for tailored interventions and community-driven initiatives to empower adolescent girls and improve their overall health outcomes.